1994
DOI: 10.1002/jlb.55.4.483
|View full text |Cite
|
Sign up to set email alerts
|

Serum components enhance bacterial lipopolysaccharide-induced tissue factor expression and tumor necrosis factor-α secretion by bovine alveolar macrophages in vitro

Abstract: We have compared the effect of bacterial lipopolysaccharide (LPS) in combination with normal adult bovine serum (NBS), fetal bovine serum (FBS), or a bovine serum fraction on tissue factor expression and tumor necrosis factor alpha (TNF-alpha) secretion by bovine alveolar macrophages. At a concentration of 1 ng/ml, bacterial LPS alone failed to induce measurable tissue factor expression by the macrophages, but the presence of FBS, NBS, or a fraction of normal pooled bovine serum isolated by ion-exchange chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
1
18
1
Order By: Relevance
“…The ability of serum to enhance the responsiveness of leukocytes from other species to LPS [32,33,41], reflects the formation of a complex between LPS and a serum LBP that is recognized by the glycosylphosphatidylinositol-anchored membrane protein, CD14 [42]. These data provide strong evidence for a similar paradigm underlying the mechanism of LPS interaction with equine neutrophils.…”
Section: Discussionmentioning
confidence: 78%
“…The ability of serum to enhance the responsiveness of leukocytes from other species to LPS [32,33,41], reflects the formation of a complex between LPS and a serum LBP that is recognized by the glycosylphosphatidylinositol-anchored membrane protein, CD14 [42]. These data provide strong evidence for a similar paradigm underlying the mechanism of LPS interaction with equine neutrophils.…”
Section: Discussionmentioning
confidence: 78%
“…Free GPIs are present in the extracellular medium in their entire form, probably secreted by the parasites. 6 We assume that macrophage enzymes like phospholipases, cleave the GPI lipid moiety, allowing its interaction with galectin-3 and the TLR signaling. Galectin-3 may play a major role in controlling cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that both TLR2 and TLR4 are involved in the NF-Bdependent signaling cascade leading to production of TNF-␣ by macrophages exposed to T. gondii GPIs (5). The membrane protein CD14 is a co-receptor that associates with TLR4 to form a receptor complex for bacterial lipopolysaccharide (LPS) (6). CD14 is involved in the recognition of lipoproteins from Mycobacterium tuberculosis by TLR2 (7).…”
mentioning
confidence: 99%
“…Since microglia represent the first line of defense against bacterial infections in the CNS parenchyma and modulating PRR expression may have implications on the extent of microglial antibacterial responses, the effects of S. aureus and PGN on CD14 protein expression in primary microglia was evaluated by Western blotting. Since serum contains sCD14 and LBP that are capable of augmenting cell responses to microbial stimuli (Cohen et al, 1995;Wright et al, 1990;Yang et al, 1994), the ability of S. aureus and PGN to modulate CD14 expression was evaluated in the absence of serum. Under these conditions, both S. aureus and PGN stimulation led to an increase in CD14 protein expression in primary WT microglia (Fig.…”
Section: Effects Of S Aureus and Pgn On Cd14 Expression In Primary Mmentioning
confidence: 99%
“…In the current study, we evaluated the relative importance of CD14 on S. aureus and PGN recognition using primary microglia isolated from CD14 KO and WT mice. Since fetal bovine serum (FBS) serves as a source of sCD14 and LPS binding protein (LBP), the latter of which facilitates the transfer of PGN to mCD14 (Cohen et al, 1995;Dziarski, 2003;Wright et al, 1990;Yang et al, 1994), we examined microglial activation in response to gram-positive stimuli under serum-free conditions to prevent any confounding effects of serum on the results obtained. The findings presented demonstrate that CD14 participates in PGN-dependent microglial activation, whereas responses to intact S. aureus are primarily CD14-independent.…”
Section: Introductionmentioning
confidence: 99%